Control of Bittercress in Florida Container Nurseries - Jeffrey G. Norcini (EDIS)
Container nursery growers frequently cite bittercress as one of their more common weed problems. Not only is it a weed concern, but bittercress can harbor insect pests. This document is ENH985, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date December 2004.